Correction: Willingness and eligibility to donate blood under 12-month and 3-month deferral policies among gay, bisexual, and other men who have sex with men in Ontario, Canada. - PLOS Global Public Health Staff (Public Library of Science (PLoS), 2023)
[This corrects the article DOI: 10.1371/journal.pgph.0001380.].